Living and dying to be counted: What we know about the epidemiology of the global adolescent HIV epidemic. (16th May 2017) - Slogrove, Amy L.; Mahy, Mary; Armstrong, Alice; Davies, Mary‐Ann
Abstract: Introduction : With increasing survival of vertically HIV‐infected children and ongoing new horizontal HIV infections, the population of adolescents (age 10–19 years) living with HIV is increasing. This review aims to describe the epidemiology of the adolescent HIV epidemic and the ability of national monitoring systems to measure outcomes in HIV‐infected adolescents through the adolescent transition to adulthood. Methods : Differences in global trends between younger (age 10–14 years) and older (age 15–19 years) adolescents in key epidemic indicators are interrogated using 2016 UNAIDS estimates. National population‐based survey data in the 15 highest adolescent HIV burden countries are evaluated and examples of national case‐based surveillance systems described. Finally, we consider the potential impact of adolescent‐specific recommendations in the 2016 WHO Consolidated Guidelines on the Use of Antiretroviral Drugs for Treating and Preventing HIV Infection. Discussion : UNAIDS estimates indicate the population of adolescents living with HIV is increasing, new HIV infections in older adolescents are declining, and while AIDS‐related deaths are beginning to decline in younger adolescents, they are still increasing in older adolescents. National population‐based surveys provide valuable estimates of HIV prevalence in older adolescents and recent surveys include data on younger adolescents. Only a few countries have nationwide electronic case‐based HIV surveillance, with the ability to provide population‐level data on key HIV outcomes in the diagnosed population living with HIV. However, in the 15 highest adolescent HIV burden countries, there are no systems tracking adolescent transition to adulthood or healthcare transition. The strength of the 2016 WHO adolescent‐specific recommendations on antiretroviral therapy and provision of HIV services to adolescents was hampered by the lack of evidence specific to this age group. Conclusions : Progress is being made in national surveillance and global monitoring systems to specifically identify trends in adolescents living with HIV. However, HIV programmes responsive to the evolving HIV prevention and treatment needs of adolescents can be facilitated further by: data disaggregation to younger and older adolescents and mode of HIV infection where feasible; implementation of tools to achieve expanded national case‐based surveillance; streamlining consent/assent procedures in younger adolescents and consensus on indicators of adolescent healthcare transition and transition to adulthood.